DEVELOPMENT OF DELAYED RELEASE PULSATILE DELIVERY SYSTEM FOR NOCTURNAL HYPERTENSION - Kartik Shah; Madhu Raj Sharma; Dr. Shailendra Sharma (Medico Research Chronicles, 1970)
The aim of the present study was to develop enalapril maleate delayed release polymer-coated pellet formulation as a time-dependent delivery for treatment of hypertension having a close relationship to the chronobiology. Extrusion spheronization technique has been used with box Behnken response surface methodology to study three different factors effect on the robustness of formation i.e. maximum drug release and minimum friability. The concentration of binder showed significant impact on pellet robustness. A further novelty of this work is the use of the combination of pH and time-dependent polymers as a single coating for the development of delayed release pellet formulation. Coating of drug matrix core pellets was optimized by applying a 2-factors 3-levels full factorial design. Continuous dissolution studies were carried out in simulated gastric, intestinal, and colonic fluid with pH 1.2, pH 4.5 and pH 6.8 media respectively. The lag time prior to the drug release was highly affected by a combination of two factors, i.e. the percentage of Eud. RL in coating polymer mixture and coating % level. This experiment demonstrates that the enalapril polymer-coated pellets could be successfully prepared by the design of pH- and time-dependent modified polymer coating to get chronopharmaceutical formulation.